Question
upstudy study bank question image url

Use la forma polar de los números complejos dados para hacer las operaciones que se piden: a) Para \( z=1-0.5 \mathrm{i} \) y \( w=3-7 \mathrm{i} \) calcule \( z w \). b) Para \( z=-36 \mathrm{i} \) y \( w=-2-i \) calcule \( z w \).

Ask by Daniels Guerrero. in Mexico
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( z \times w = -0.442 - 8.483i \) b) \( z \times w = -36 + 72i \)

Solution

Alright, I need to solve these complex number multiplication problems using their polar forms. Let's tackle them one by one. **Problem a:** Given \( z = 1 - 0.5i \) and \( w = 3 - 7i \), calculate \( z \times w \). First, I'll convert both complex numbers to their polar forms. The polar form of a complex number \( z = a + bi \) is given by \( z = r(\cos \theta + i \sin \theta) \), where \( r = \sqrt{a^2 + b^2} \) and \( \theta = \arctan\left(\frac{b}{a}\right) \). **For \( z = 1 - 0.5i \):** - \( r_z = \sqrt{1^2 + (-0.5)^2} = \sqrt{1 + 0.25} = \sqrt{1.25} \approx 1.118 \) - \( \theta_z = \arctan\left(\frac{-0.5}{1}\right) = \arctan(-0.5) \approx -26.565^\circ \) or \( 333.435^\circ \) (since it's in the fourth quadrant) **For \( w = 3 - 7i \):** - \( r_w = \sqrt{3^2 + (-7)^2} = \sqrt{9 + 49} = \sqrt{58} \approx 7.62 \) - \( \theta_w = \arctan\left(\frac{-7}{3}\right) \approx -66.8^\circ \) or \( 293.2^\circ \) (since it's in the fourth quadrant) Now, to multiply two complex numbers in polar form, I multiply their magnitudes and add their angles: - \( r_{zw} = r_z \times r_w = 1.118 \times 7.62 \approx 8.5 \) - \( \theta_{zw} = \theta_z + \theta_w = -26.565^\circ + (-66.8^\circ) = -93.365^\circ \) So, \( z \times w \) in polar form is approximately \( 8.5(\cos(-93.365^\circ) + i \sin(-93.365^\circ)) \). To convert this back to rectangular form: - \( \cos(-93.365^\circ) \approx -0.052 \) - \( \sin(-93.365^\circ) \approx -0.998 \) - Therefore, \( z \times w \approx 8.5 \times (-0.052) + 8.5 \times (-0.998)i \approx -0.442 - 8.483i \) **Problem b:** Given \( z = -36i \) and \( w = -2 - i \), calculate \( z \times w \). First, let's express both complex numbers in standard form: - \( z = 0 - 36i \) - \( w = -2 - i \) Now, multiply them: - \( z \times w = (0 - 36i)(-2 - i) = 0 \times (-2) + 0 \times (-i) + (-36i) \times (-2) + (-36i) \times (-i) \) - \( = 0 + 0 + 72i + 36i^2 \) - Since \( i^2 = -1 \), \( 36i^2 = 36 \times (-1) = -36 \) - So, \( z \times w = 72i - 36 \) Therefore, \( z \times w = -36 + 72i \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Primero, transformemos los números complejos a su forma polar y luego realizaremos las operaciones. a) Para \( z = 1 - 0.5i \): 1. El módulo de \( z \) es \( |z| = \sqrt{1^2 + (-0.5)^2} = \sqrt{1 + 0.25} = \sqrt{1.25} = \frac{\sqrt{5}}{2} \). 2. El argumento de \( z \) es \( \theta_z = \tan^{-1}\left(\frac{-0.5}{1}\right) \approx -0.4636\) radianes. 3. Por lo tanto, la forma polar de \( z \) es \( z = \frac{\sqrt{5}}{2} \text{cis}(-0.4636) \). Para \( w = 3 - 7i \): 1. El módulo de \( w \) es \( |w| = \sqrt{3^2 + (-7)^2} = \sqrt{9 + 49} = \sqrt{58} \). 2. El argumento de \( w \) es \( \theta_w = \tan^{-1}\left(\frac{-7}{3}\right) \approx -1.1659 \) radianes. 3. Por lo tanto, la forma polar de \( w \) es \( w = \sqrt{58} \text{cis}(-1.1659) \). Ahora, para \( zw \): \[ zw = |z||w| \text{cis}(\theta_z + \theta_w) = \left(\frac{\sqrt{5}}{2} \cdot \sqrt{58}\right) \text{cis}(-0.4636 - 1.1659) = \frac{\sqrt{290}}{2} \text{cis}(-1.6295). \] b) Para \( z = -36i \): 1. El módulo de \( z \) es \( |z| = 36 \). 2. El argumento de \( z \) es \( \theta_z = -\frac{\pi}{2} \). 3. Por lo tanto, la forma polar de \( z \) es \( z = 36 \text{cis}\left(-\frac{\pi}{2}\right) \). Para \( w = -2 - i \): 1. El módulo de \( w \) es \( |w| = \sqrt{(-2)^2 + (-1)^2} = \sqrt{4 + 1} = \sqrt{5} \). 2. El argumento de \( w \) es \( \theta_w = \tan^{-1}\left(\frac{-1}{-2}\right) + \pi \approx -2.6779 \) radianes. 3. Por lo tanto, la forma polar de \( w \) es \( w = \sqrt{5} \text{cis}\left(-2.6779\right) \). Ahora, para \( zw \): \[ zw = |z||w| \text{cis}(\theta_z + \theta_w) = (36 \cdot \sqrt{5}) \text{cis}\left(-\frac{\pi}{2} - 2.6779\right) = 36\sqrt{5} \text{cis}\left(-3.1416\right). \] Finalmente, \( zw \) se simplifica como \( zw = -36\sqrt{5} \).

Related Questions

Latest Other Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy